Breast Self-Examination; Significant tool in early detection of Breast Cancer - Khan, Saima; Ahmed , Sadaf; Sultana, Nelofer; Noushad , Shamoon (International Journal of Endorsing Health Science Research, 2014)
This evidence based study is to provide the awareness of breast self examination; its outcomes and significance. There is a never matching increase noted in the incidences of breast cancer worldwide. Pakistani women are on top of the list in the region to develop this disease and it has also been observed that they diagnose to have higher grade disease in early age. Early detection followed by timely treatment is the best prognosis for long term survival. This a retrospective study in which the data was gathered through questionnaire for the selected variables. Out of 100 patients 49 were doing BSE while 51 were unaware of breast self-examination. Out of these 49% , 42% were doing BSE randomly,2% were doing monthly,3% were doing weekly while 2% were doing on daily bases, and 24 (49%) patients were found to have microscopically confirmed carcinoma and 12 (24%) were found to have negative microscopic exams remaining 13 (27%) patients who were doing BSE were not gone through microscopic exam. Breast self-examination is the simplest tool that can play an important role in the detection of breast cancer. There is need to encourage BSE practices among the women along with the development of awareness program to make it successful.